PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 IV KOTO - Putri RY, Risky Aryska; Haida Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was prompted by the low level of problem-solving skills in mathematics among students in Year 8 at SMP Negeri 1 IV Koto. One possible solution to this problem is the implementation of the cooperative learning model CORE (Connecting, Organizing, Reflecting, Extending), which encourages students to actively build knowledge by connecting concepts, organizing information, reflecting, and developing understanding. The aim of this study is to determine the effect of implementing the CORE cooperative learning model on students' ability to solve mathematical problems compared with conventional learning. This study is a pre-experiment with a Static Group Comparison Design. The population of the study is all students in Year 8 at SMP Negeri 1 IV Koto. Sampling was done randomly after passing the normality, homogeneity, and equality of means tests. The research sample consisted of class VIII.4 as the experimental class and class VIII.2 as the control class. The research instrument was a test of essay-type mathematical problem-solving ability. Data analysis was performed using t-tests, reinforced with the help of Minitab software. The results of the study show that the calculated t-value of 4.81 is greater than the t-table value of 1.68 at a significance level of α = 0.05. The Minitab analysis also showed that P-Value = 0.000 < 0.05, so H₀ was rejected and H₁ was accepted. It can therefore be concluded that the implementation of the cooperative learning model CORE has a significant impact on the ability of students in class VIII of SMP Negeri 1 IV Koto to solve mathematical problems compared to conventional learning.